Primary and Secondary Immunodeficiency Diseases in Oncohaematology: Warning Signs, Diagnosis, and Management - Sánchez-Ramón, Silvia; Bermúdez, Arancha; González-Granado, Luis Ignacio; Rodríguez-Gallego, Carlos; Sastre, Ana; Soler-Palacín, Pere; , the ID-Signal Onco-Haematology Group; Allende, Luis; Alsina, Laia; Bielsa, Ana María; Calleja-Antolín, Sara; Cámara, Carmen; et al. (Frontiers in Immunology, 2019)
Background: Immunodeficiencies (ID), in particular primary immunodeficiencies (PID), are often associated with haematological manifestations, such as peripheral cytopenias or lymphoproliferative syndromes. Early diagnosis and management have significant prognostic implications. Secondary immunodeficiencies (SID) may also be induced by oncohaematological diseases and their treatments. Haematologists and oncologists must therefore be aware of the association between blood disorders and cancer and ID, and be prepared to offer their patients appropriate treatment without delay. Our aim was to define the warning signs of primary and secondary IDs in paediatric and adult patients with oncohaematological manifestations. Methods: A multidisciplinary group of six experts (2 haematologists, 2 immunologists and 2 paediatricians specializing in ID) conducted a literature review and prepared a document based on agreements reached an in-person meeting. An external group of 44 IDs specialists from all over Spain assessed the document and were consulted regarding their level of agreement. Results: This document identifies the haematological and extra-haematological diseases that should prompt a suspicion of PIDs in adults and children, in both primary care and haematology and oncology departments. Cytopenia and certain lymphoproliferative disorders are key diagnostic pointers. The diagnosis must be based on a detailed clinical history, physical exploration, complete blood count and standard laboratory tests. The immunological and haematological tests included in the diagnostic process will depend on the care level. Patients who are candidates for immunoglobulin replacement therapy must be carefully selected, and treatment should be offered as soon as possible to avoid the development of complications. Finally, this document recommends procedures for monitoring these patients. Conclusions: This document combines scientific evidence with the opinion of a broad panel of experts, and emphasizes the importance of an early diagnosis and treatment to avoid complications. The resulting document is a useful tool for primary care physicians and specialists who see both adult and paediatric patients with oncohaematological diseases.